Etkinlik Yönetimi Uygulamalarında Yaratıcı Rekabet Ve Sosyal Medyanın Entegrasyonu - Akay, Rafet Aykut (The Turkish Online Journal of Design Art and Communication, 2014)
Events are one of the most important and preferred practices of public relations discipline. The importance of event practices rises everyday with the opportunities of improving technology, and becomes much more preferable. Events becoming an important tool leads a growth in the number of event agencies, which results in a big sector special to events. There is also a challenging competition between the event agencies in the growing event sector. Diversity, which comes as a result of the growth in event sector and improvements in technology, brings extraordinary and creative dimensions to event practices. Social media networks, which are improving very fast especially on the last few years, become a very important and entertaining base for event practices, and social media and digital platforms also become much more usable. The comprehensive change in event management, digitalbased practices which can be considered as the proof of this change, and the integration of these practices to the social media with examples from the event sector, are going to be analyzed within this study.
Keywords: Etkinlik Yönetimi; Sosyal Medya; Dijital Uygulamalar; Event Management; Social Media; Digital Practices